Bamboo- and pig-derived biochars reduce leaching losses of dibutyl phthalate, cadmium, and lead from co-contaminated soils. (May 2018) - Qin, Peng; Wang, Hailong; Yang, Xing; He, Lizhi; Müller, Karin; Shaheen, Sabry M.; Xu, Song; Rinklebe, Jörg; Tsang, Daniel C.W.; Ok, Yong Sik; Bolan, Nanthi; Song, Zhaoliang; et al.
Abstract: Biochar effect on the potential mobility of dibutyl phthalate (DBP), cadmium (Cd), and lead (Pb) in co-contaminated soils is not well investigated. A laboratory leaching study was conducted to evaluate the effect of biochars derived from bamboo (BB) and pig (PB) on the leachability of DBP, Cd, and Pb through soil columns packed with two soils with low or high organic carbon content (LOC; 0.35% C: HOC; 2.24% C) and spiked with DBP, Cd, and Pb. Application of PB to the LOC soil significantly ( P < 0.05) reduced the leaching loss by up to 88% for DBP, 38% for Cd, and 71% for Pb, whereas its impact was insignificant in the HOC soil. The higher efficacy of PB in reducing the leaching of DBP, Cd, and Pb in the LOC soil than that of BB might be related to PB's higher specific surface area, surface alkalinity, pH, and mineral contents compared to those of BB. Co-contamination of Cd and Pb enhanced leaching of DBP in the LOC soil treated with PB, possibly by competition for the sorption sites. Leaching of DBP, Cd, and Pb were significantly ( P < 0.05) higher in the LOC soil than in the HOC soil. This study revealed that the effectiveness of biochars was dependent on the soil organic carbon content. Application of PB to the LOC soil was effective in reducing the leaching risk of DBP, Cd, and Pb. Highlights: Pig biochar reduced leaching of DBP, Cd, and Pb in the low organic carbon (LOC) soil. Contaminant leaching was higher in the LOC soil than in the high organic carbon soil. Existence of Cd and Pb enhanced mobility of DBP in the pig biochar-treated LOC soil. Alkalinity and phosphate in biochar controlled the leaching loss of Cd and Pb. Impact of pig biochar on leaching of DBP, Cd, and Pb is stronger than bamboo biochar.